2009
DOI: 10.1080/14733140802655992
|View full text |Cite
|
Sign up to set email alerts
|

Client‐centred therapy for severe childhood abuse: A case study

Abstract: Aims: This case study demonstrates the experience of client change in non-directive client-centred therapy for a client ('Mac') who had experienced severe and repeated childhood abuse within an institutional care setting and shows how complex posttraumatic stress involving difficulties in identity, problems forming and maintaining non-abusive interpersonal relationships were encountered within the therapy. Method: The data were taken from the detailed notes of 160 sessions of client-centred therapy. Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…Accordingly, Wilson, Becker, & Tinker (1995) observe that posttraumatic stresstargeted treatments tend to have little effect on overall psychological functioning for adult survivors of childhood trauma as the complex presentation of survivors requires comprehensive treatment approaches across a range of psychosocial functioning. As survivors experience a complex presentation of disturbances (Clemans, 2004;Paivio & Nieuwenhuis, 2001) including changes to consciousness, emotional control, self-perception, perception of others, and systems of meaning (Freyd, 1996), cognitive or behavioural treatment approaches are limited (Murphy, 2009). Currently, a void exists both in the literature and therefore in practice concerning treatment options for adult survivors of childhood trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Wilson, Becker, & Tinker (1995) observe that posttraumatic stresstargeted treatments tend to have little effect on overall psychological functioning for adult survivors of childhood trauma as the complex presentation of survivors requires comprehensive treatment approaches across a range of psychosocial functioning. As survivors experience a complex presentation of disturbances (Clemans, 2004;Paivio & Nieuwenhuis, 2001) including changes to consciousness, emotional control, self-perception, perception of others, and systems of meaning (Freyd, 1996), cognitive or behavioural treatment approaches are limited (Murphy, 2009). Currently, a void exists both in the literature and therefore in practice concerning treatment options for adult survivors of childhood trauma.…”
Section: Introductionmentioning
confidence: 99%
“…There is a small but growing body of evidence in support of trauma‐focused work within person‐centred therapy. Some of this evidence is based on qualitative case studies (Murphy, ; Tickle & Murphy, ) showing the benefits of person‐centred therapy with clients traumatised through childhood abuse and domestic abuse. Added to this, research in the field of Focusing‐Oriented Therapy (Coffeng, ; Rappaport, ; Santen, ) showed how a person‐centred and experiential approach worked with traumatised young people.…”
Section: Brief Literature Review For Pce Therapies and Trauma‐focusedmentioning
confidence: 99%
“…Therapist researchers have researched the therapy experiences of clients who are also survivors of CSA (e.g. Dale, Allen & Measor, 1998;Etherington, 2000Etherington, , 2001bHirakata, 2009;Murphy, 2009;Wosket, 1999). These writers, and many others, have provided a background for our shared understanding of the project of writing reflectively about our research conversation.…”
Section: How This Paper Came Aboutmentioning
confidence: 99%